Effective and selective adsorption of As(III) via imprinted magnetic Fe3O4/HTCC composite nanoparticles. Issue 1 (February 2017) - Song, Xiaoli; Li, Ling; Geng, Zhirong; Zhou, Lei; Ji, Lijun
Graphical abstract: Highlights: As(III) imprinted magnetic Fe3 O4 HTCC composite nanoparticles was successfully prepared via micro emulsions method. As(III)-IMHNPs showed high removal efficiency for As(III), furthermore, compared with NIMHNPs, the effects of coexisting ions on As(III) removal were reduced, indicating an enhanced selectivity adsorption of As(III) by As(III)-IMHNPs. Adsorption efficiency of As(III) was still above 75% even after 10 recycles. Abstract: As(III) imprinted magnetic Fe3 O4 N-(2-hydroxyl)propyl-3-trimethyl ammonium chitosan chloride (HTCC) composite nanoparticles (As(III)-IMHNPs) was prepared via micro-emulsions method. The As(III)-IMHNPs was efficient and selective to adsorb As(III) with the maximum adsorption capacity at 11.52 mg/g which got in 5 mg/L As(III) solution. With the imprinting of As(III), the selectivity of As(III)-IMHNPs was enhanced and the effects of competing ions on As(III) removal were greatly reduced. Moreover, the nanoparticle showed good regeneration performance, and its adsorption efficiency of As(III) was still above 75% even after 10 recycles. The adsorption behavior of As(III) on As(III)-IMHNPs could be better described by pseudo-second-order model, which indicated that the adsorption was promoted by a chemical process.